Usulan Perubahan Penugasan Operator dalam Upaya Meningkatkan Output Produksi dengan Metode Simulasi (Studi Kasus di PT Central Texindo) - ., admin (Zenit, 2015)
PT Central Texindo is a knitting company located in Padalarang Bandung. Currently the company is facing problems in the knitting department. The problem faced by the company is thatinstallation time cones are long enough so that the output of the company is less than optimal. In addition there is also the production disruptions that can not be avoided that thread broke during ongoing production. The required data, data on the number and type of machine used, the data processing time of each machine, cones installation time data, event data and time the thread breaking these connections, the data engine oil changes, and gray cloth production data. After the data collected, conducted runs test and goodness of fit test. Next conducted model using software Promodel. Simulation in PT Central Texindo belong to the non-terminating simulation. The proposal is made that a change of assignment operators in an effort to increase production output with the same number of operators. Assignment operator is an operator currently supervise 3 machines, which occurs when a thread broke operator must immediately make improvements to the production process can take place again. In addition, operators must perform the replacement cones every machine theyoversee. Average gray cloth which can be produced as many as 555,632 companies roll per day. The scenario is to create assignment two operators supervise 6 machines, three operators supervise 9 machines, and four operators supervise 12 machines. The results obtained indicate that the averageoutput of the scenarios four operators supervise 12 machines produce more output. The increase in output is obtained that is equal to 17,42% or average production output 652,421 roll per day. Proposed assignment operator is only limited to the four operators who supervise 12 machines because of the location of the installation of the cones are limited or not allowed to exceed 4 operators.Keywords: Runs Test, Goodness Of Fit, Simulation, Increased Production Output